Oedipus' Tragedy: An Arabic Reinterpretation - Saleh Al-Ghoreibi, Fathia (Gezira Journal of Educational Sciences and Humanities; مجلد 14 عدد 1 (2017), 2017)
Ali Ahmed Bakathir was keen to reflect Arabs' and Muslims' issues in his literary works. In his belief, history and myth, which are rich in symbols, can be a major source of inspiration to the man of letters. The present study focuses on Bakathir's use of the Greek myth of Oedipus as treated by Sophocles in his play Oedipus Rex . To adapt the myth to the Muslim faith and beliefs, the writer introduces certain changes to his version. The paper examines these changes both in content and form and shows Bakathir's reinterpretation of the classical tragedy after ridding it of the legendary and prophetical context and making it approach the ordinary human life.  The study also deals with Bakathir's use of standard Arabic, a neutral language, as an attempt to create a medium that will unite Arab audiences. The researcher offers an overall evaluation of Bakathir's success or otherwise in fulfilling his objectives of writing the play.